Register Penggunaan Bahasa pada Cerita Pendek Berjudul Filosofi Kopi Karya Dee Lestari : Kajian Sosiolinguistik dan Semiotika Budaya - Vani Indra Pramudianto; Kuntara Kuntara (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to describe the form, meaning, and socio-cultural function of the register of language use in the short story Filosofi Kopi by Dee Lestari. The method used is descriptive qualitative with content analysis techniques, Halliday's register theory, and Lotman's cultural semiotics. The results of the study show that the form of register in this short story includes words (espresso, latte, cappuccino, macchiato), nominal phrases (filosofi kopi, signature coffee, kopi tiwus), idiomatic phrases (kopi paling flirtit), and metaphors (espresso as a life without nonsense, latte as a warm hug). The meaning of the register is divided into primary meaning (literal) and secondary meaning (cultural and symbolic) which construct the values ​​of masculinity, gentleness, beauty, spirituality, and idealism of the characters. The socio-cultural functions of the register include community identity, expressive, evaluative, symbolic, narrative aesthetic, and ideological functions. This research supports Halliday's theory on the relationship between register and situational context, as well as Lotman's theory, which views literary language as a secondary modeling system that represents social and cultural realities. The results are expected to enrich the study of literary sociolinguistics and serve as authentic and contextual teaching materials for Indonesian language and literature in secondary schools.